Induction of New Aromatic Polyketides from the Marine Actinobacterium Streptomyces griseorubiginosus through an OSMAC Approach - Víctor Rodríguez Martín-Aragón; Francisco Romero Millán; Cristina Cuadrado; Antonio Hernández Daranas; Antonio Fernández Medarde; José M. Sánchez López (Marine Drugs, 2023)
Using the OSMAC (One Strain Many Compounds) approach, the actinobacterium Streptomyces griseorubiginosus, derived from an unidentified cnidarian collected from a reef near Pointe de Bellevue in Réunion Island (France), was subjected to cultivation under diverse conditions. This endeavour yielded the isolation of a repertoire of 23 secondary metabolites (1–23), wherein five compounds were unprecedented as natural products (19–23). Specifically, compounds 19 and 20 showcased novel anthrone backbones, while compound 23 displayed a distinctive tetralone structure. Additionally, compounds 21 and 22 presented an unusual naphtho [2,3-c]furan-4(9H)-one chromophore. Interestingly, the detection of all these novel compounds (19–23) was exclusively achieved when the bacterium was cultured in FA-1 liquid medium supplemented with the epigenetic modifier γ-butyrolactone. The elucidation of the structural features of the newfound compounds was accomplished through a combination of HRESIMS, 1D and 2D NMR spectroscopy, as well as QM-NMR (Quantum Mechanical—Nuclear Magnetic Resonance) methods and by comparison with existing literature. Moreover, the determination of the relative configuration of compound 23 was facilitated by employing the mix-J-DP4 computational approach.